The Relationship Between Students' Cognitive Achievement in PAI Subjects and Their Religious Attitudes at SDN 90 Cibiru Panyileukan District Bandung - Robaeah, Wilam Nafilah; Karman, Karman; Nasir, Tatang Muh; Turwanto, Teguh; Yulistiawati, Lilis (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2023)
It cannot be denied, someone who has high religious knowledge is directly proportional to their high religious attitude, and vice versa. That is, to what extent they can accept the attainment of religious knowledge that they have to apply. This study aims to: 1) determine students' cognitive achievement in PAI subject in class VII SDN 90 Cibiru; 2) knowing the religious attitudes of students in PAI subjects in class VII SDN 90 Cibiru; and 3) knowing the relationship between students' cognitive achievement in PAI subjects and their religious attitudes in class VII SDN 90 Cibiru. The approach used in this study is a quantitative approach to the correlative descriptive method. Analysis of the data used through statistical calculations. Data collection techniques used were questionnaires, observations, documentation studies, literature studies, and interviews. The sample used was class VII students. Where sampling was used 10% -15% of the existing population, that is, from 257 populations, 30 samples were used. The results of the study show that: 1) based on the calculation of cognitive achievement of students, the price (81.99) is identified in the very good category; 2) The students' religious attitudes based on calculations obtained prices (3.58) identified in the high category; and 3) the relationship between students' cognitive achievement and their religious attitude through Spearman's rank correlation test obtained the correlation value (0.188) assumed to be in the very low relationship category, then compared with the price of ρ table (0.306) then Ho is accepted and Ha is rejected. Then determine the price of t with a: 5%. obtained the value of t count (1.01) and t table (1.697).